Fixation of the shorter cementless GTSTM stem: biomechanical comparison between a conventional and an innovative implant design - Nadorf, Jan; Thomsen, Marc N.; Gantz, Simone; Sonntag, Robert; Kretzer, Jan Philippe (Archives of orthopaedic and trauma surgery, 2014)
Conventional cementless total hip arthroplasty already shows very good clinical results. Nevertheless, implant revision is often accompanied by massive bone loss. The new shorter GTS™ stem has been introduced to conserve femoral bone stock. However, no long-term clinical results were available for this implant. A biomechanical comparison of the GTS™ stem with the clinically well-established CLS® stem was therefore preformed to investigate the targeted stem philosophy.